Dissatisfaction with body image among adolescent students: Association with socio-demographic factors and nutritional status insatisfação com a imagem corporal entre adolescentes estudantes: Associação com fatores sociodemográficos e estado nutricional - Coqueiro R.S. (2014)
This article seeks to determine the prevalence of dissatisfaction with body image and its association with socio-demographic factors and nutritional status among adolescents. The following socio-demographic data, anthropometric variables, and perception of body image (n = 660) were collected. The prevalence of dissatisfaction with body image was 71.4%. Girls wished to reduce the size of their body silhouette, whereas boys wished to increase it. The desire to reduce body size was positively associated with female gender, with increased waist circumference and with excess weight. On the other hand, the desire to increase body size was negatively associated with the female gender and waist circumference, and was positively associated with ages 16, 17 and 18 + 19 years. Dissatisfaction with body image is highly prevalent among adolescents, though it is manifested differently in boys and girls. Increased abdominal fat, excess weight and female gender were predictors of dissatisfaction due to excess weight, and male gender and advanced age were predictors of dissatisfaction due to thinness.